The When and Whereabouts of Gender Hiring Discrimination - Bygren, Magnus; Erlandsson, Anni; Gahler, Michael (SAGE Publications, 2025)
The aim of this article is to explore the circumstances leading employers to discriminate by gender and parenthood, contributing to the broader aim at increasing our understanding about the mechanisms underlying gender inequality in the labor market. Previous Swedish (and many international) studies show that employers are about equally likely to hire men and women. These results tend to refer, however, to data based on aggregates of branches, occupations and sectors. Statistical power is commonly low when results are broken down by segments. Studies showing no employer discrimination at the aggregate level may thus hide discrimination in certain segments. There are reasons to expect discrimination by gender and parenthood to vary depending on context and we explore this by relating variation in employer behavior to variation in demographic (gender) composition and qualification level in the occupation applied for. In this study, a large-scale experimental correspondence test design is employed, and non-authentic applications-with gender and parenthood randomly assigned to job applications-are sent to job openings in the Swedish labor market, including information on a total of 6,755 job applications in 15 occupations. The results show no indication of discrimination based on gender or parenthood in this early step of the recruitment process, and this is regardless of whether the occupation is dominated by either gender or is gender balanced.